Effect of the Quezon City controlled dumping facility (QCCDF) leachate on the water quality of a segment of Marikina river - Chounlamany, Vanseng (College of Engineering, University of the Philippines Diliman, 2014)
Marikina River in the Philippines has been subjected to substantial pollution from a variety of point and non-point sources. One of the point source that discharges to the river is Payatas creek that carries leachate from a nearby landfill. In addition, domestic waste from local communities also gels discharged into the river through the same creek. This study involves a comprehensive investigation of the river water quality, landfill leachate quality and the water quality of two creeks that drain to Marikina River to examine the sources of pollution and estimate the pollution loading from the creeks to Marikina River. It was found that leachate from QCCDF is highly polluted compared to other tropical Asian landfill leachate and QCCDF is in the methanogenic phase. Marikina River is suitable for agriculture purpose only based on DENR Administrative Oder No. 34 (DAO 34) Philippines. Application of multivariate statistical techniques to the water quality data shows that the 10-month period can be clustered into three temporal clusters and the 5 sampling sites can be clustered in to 4 groups. Principal Component Analysis shows that the highest state of pollution is observed at the sampling station immediately downstream of Payatas creek outfall while the river shows some ability to self-purify in the downstream direction. The dry season generally represents a high degree of pollution in the river whereas the rainy season corresponds to a relatively lower state of pollution. PCA results indicate that pH and NO3 have a little influence on the water quality state of Marikina River while turbidity, TSS and SO42- are important only during wet season. On the other hand, TDS, Cl, COD, BOD and PO43- are the most significant water quality parameters for Marikina River and confirm anthropogenic pollution as the main form of river pollution. Pollution loading analysis shows significant addition of organic matter into Marikina River from Payatas creek. The influence of municipal wastewater creek is not as high as Payatas creek with respect to the addition of organic matter. River COD levels are tripled during the dry season due to continuous addition of chemical species from landfill and domestic waste to river.